2020
DOI: 10.1016/j.bonr.2020.100293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denosumab versus teriparatide in glucocorticoid-induced osteoporosis patients with prior bisphosphonate treatment

Abstract: Introduction Osteoporosis is one of the serious adverse effects associated with glucocorticoid therapy. Although bisphosphonates have been used for glucocorticoid-induced osteoporosis (GIO), some patients have shown an inadequate response. In such cases, denosumab or teriparatide are used. However, there is no consensus on which of these two drugs is superior. We prospectively compared denosumab's and teriparatide's effects on the bone mineral density (BMD) in GIO patients with prior bisphosphonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…In the DATA extension study, which was conducted in bisphosphonate-naïve women with postmenopausal osteoporosis, both the denosumab- and teriparatide-treated groups showed significant increases from baseline in BMD at the lumbar spine, femoral neck, and total hip, with no significant differences between the two groups ( 14 ). On the other hand, our earlier study demonstrated that teriparatide has some advantages over denosumab in GIO patients with prior bisphosphonate treatment ( 15 ). The discrepancy in the results may be due to the different backgrounds of the patients addressed in each study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the DATA extension study, which was conducted in bisphosphonate-naïve women with postmenopausal osteoporosis, both the denosumab- and teriparatide-treated groups showed significant increases from baseline in BMD at the lumbar spine, femoral neck, and total hip, with no significant differences between the two groups ( 14 ). On the other hand, our earlier study demonstrated that teriparatide has some advantages over denosumab in GIO patients with prior bisphosphonate treatment ( 15 ). The discrepancy in the results may be due to the different backgrounds of the patients addressed in each study.…”
Section: Discussionmentioning
confidence: 98%
“…This study was conducted from 2014 to 2021 at Kindai University Hospital (Osaka, Japan). The original study ( 15 ) was a 24-month, prospective, open-label, non-randomized clinical trial. The present study’s inclusion and exclusion criteria were the same as those of the original study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teriparatide is an active form of parathyroid hormone (PTH) consisting of the N-terminal 34 amino acids. In the clinical survey, teriparatide significantly increases the expression of bone formation markers and bone mass density of GIOP patients [ 159 160 161 ]. Intermittent use of teriparatide facilitates osteoblast production, increases TNAP activity [ 162 ], and promotes WNT signaling by reducing WNT signaling inhibitors, such as Sost , Dkk1 , sFRP-1 , and axin-2 [ 49 163 164 165 ].…”
Section: T Reatment Options For Glucocorticoid-induced Osteoporosismentioning
confidence: 99%
“…However, due to off-target and other side effects, these drugs are far from satisfactory in use ( Whittier and Saag, 2016 ; Chotiyarnwong and McCloskey, 2020 ). For example, gastrointestinal discomfort was often found in the patients with oral bisphosphonates, meanwhile, mandible osteonecrosis, nephrotoxicity, and the increased risk of venous thrombosis were also found in the patients with intravenous bisphosphonates ( Cummings et al, 2009 ; Hirooka et al, 2020 ). Therefore, there is an urgent clinical need for a new effective treatment strategy for GIOP treatment.…”
Section: Introductionmentioning
confidence: 99%